(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Public satisfaction is an important indicator in assessing the quality of public services, because it reflects the extent to which user expectations are met by the services provided. This study aims to analyze the level of community satisfaction with sports facilities at the INGUB Klender Stadium, East Jakarta. This research uses a quantitative approach with descriptive methods. Data were obtained through distributing questionnaires to 75 respondents who are active users of sports facilities at the stadium. The research instrument was prepared based on the SERVQUAL model with six main indicators, namely physical evidence (tangible), reliability, location accessibility, security and safety (assurance), empathy, and conformance to expectations (conformance). The results showed that in general the community has a very high level of satisfaction with sports facilities at the INGUB Klender Stadium. 60% of respondents stated that they were very satisfied and 38.67% stated that they were satisfied. The factor with the highest level of satisfaction is location accessibility (74.67%), followed by security and safety and empathy (65.33% each). This finding indicates that the sports facilities have met the expectations of the community, both in terms of service quality and convenience of use. The high level of community satisfaction indicates that the management of sports facilities at the INGUB Klender Stadium has been running well and properly